2009
DOI: 10.1002/hec.1394
|View full text |Cite
|
Sign up to set email alerts
|

Investing time in health: do socioeconomically disadvantaged patients spend more or less extra time on diabetes self‐care?

Abstract: Summary Background Research on self-care for chronic disease has not examined time requirements. TRIAD, a multi-site study of managed care patients with diabetes, is among the first to assess self-care time. Objective To examine associations between socioeconomic position and extra time patients spend on foot care, shopping/cooking, and exercise due to diabetes. Data 11,927 patient surveys from 2000–01. Methods Bayesian two-part models were used to estimate associations of self-reported extra time spent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 44 publications
6
36
1
Order By: Relevance
“…Using surveys and phone interviews, Ettner et al [26] studied the impact of socioeconomic status on time spent on self care for people with diabetes, looking specifically at time spent on foot care, shopping for and cooking special foods, and undertaking recommended exercise. Ettner et al found that those spending "extra time" on HRA as a result of having diabetes spent on average an extra 13.41 minutes daily on foot care, 38.57 minutes on exercise and 42.42 minutes on shopping and cooking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using surveys and phone interviews, Ettner et al [26] studied the impact of socioeconomic status on time spent on self care for people with diabetes, looking specifically at time spent on foot care, shopping for and cooking special foods, and undertaking recommended exercise. Ettner et al found that those spending "extra time" on HRA as a result of having diabetes spent on average an extra 13.41 minutes daily on foot care, 38.57 minutes on exercise and 42.42 minutes on shopping and cooking.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, studies included for review suggest that over a 24 hour period patients are likely to spend 86 minutes on HRA [20]; less time if they have had a stroke [21], more time if they have diabetes [18,19,26]. If patients also engage in exercise they spend in the order of 35 minutes each day.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies on the effect of the level of education on diabetes health outcomes have found differences regarding the time spent managing the condition and the degree of adherence to prescribed treatment [47,48]. This paper quantifies the size of the reduction in earnings that may be attributed to diabetes onset.…”
Section: Discussionmentioning
confidence: 96%
“…15 Self-testing of blood glucose requires time and therefore an economic cost that lower-income patients may not be able to afford, 16 yet a recent study demonstrated that extra time spent on self-care activities was greater in traditionally disadvantaged patients. 17 If patients are vigilant about ambulatory glucose monitoring and note worsening glycemic control, medication intensification may be initiated sooner with better health outcomes long-term. Similarly, faithful adherence to appointments may prompt health care providers to attend to problems sooner, before complications arise.…”
Section: Discussionmentioning
confidence: 99%